Changing Participation and Identity in Writing Transition: A Case Study - Lee Lai Fong (UiTM Publisher, 2012)
This study investigates the changing participation and identity in the writing transition of English as a Second Language (ESL) students from secondary school to pre university and to higher education from a sociocultural theory perspective. The data for this study was obtained from interviews, personal narratives, class observations and samples of students' essays. The students were followed for a period of one and a half year. The findings reveal that in learning to write in the different cultures of writing, the students participated in different ways as demonstrated by their changing identity throughout the transition process. The students constantly reinvented their self or identity in order to participate in the different writing cultures. Their different participation and identity were attributed to their agency: personal histories, different motives which influenced their writing. Their histories also played a role in how well they participated in writing. This study contributes to the understanding of the learning of writing as a form of participation in which students have the power, i.e. agency to act and react in certain ways and the identity they form in writing has a bearing on their writing success.